The Future of the 'culture and trade debate' : a legal outlook - Neuwirth, Rostam (2013)
Suggests that the recent emergence of the concept of creative economy can be regarded as a new opportunity to rethink not only the scope and content of the cultural and trade debate but also the principal features of the role of law in tackling the important governance challenges that lie ahead.